Resposta da comunidade de vespas e abelhas solitárias (Insecta: Hymenoptera) ao uso da terra - Batista, Michela Costa (2010)
Tropical landscapes are characterized by different land-use types such as agroecosystems and forest remnants with varying anthropization levels. Several species inhabiting forest remnants interact with agroecosystems, but their contribution to biodiversity conservation is unclear. Communities of solitary wasps and bees (Insecta: Hymenoptera) play a key role in agroecosystem functioning and these organisms have been used as bioindicators of environmental quality. Crops benefit from the ecosystem services of pest biological control and pollination provided by solitary wasps and bees, respectively. Additionally, forest fragments in the vicinity of crops can enhance natural biological control and pollination. We evaluated the species richness of solitary wasps and bees over time in a gradient of decreasing land use intensity formed by: pastures; alley croppings; young fallows (8 years old); and old fallows (20 years old). The similarity of wasps and bees‟ communities according to land-use was also evaluated. Moreover, the seasonal variation of the abundance of solitary wasps and bees as well as their communities‟ composition in the four land-use types was studied. The influence of the distance from a forest fragment to a maize field on species richness and abundance of predatory solitary wasps and its relation with the biological control of the fall armyworm (Spodoptera frugiperda Smith) was analysed. Old fallows had higher species richness of wasps and bees in comparison to the remaining land use types. Young fallows, alley croppings and pastures had similar communities of wasps and bees. Population densities of wasps and bees, in general, were not influenced by land use. However, the faunistic composition of some species of solitary wasps and bees varied with land use. The abundance of solitary wasps and bees varied throughout time with peeks in January (bees) and June and July (wasps). Moreover, the temporal variation of wasps‟ abundance (but not bees‟ abundance) was affected by land use. Predatory solitary wasps‟ abundance (but not species richness) decreased, while the fall armyworm abundance increased with increasing distance from the forest fragment. We conclude that solitary bees and wasps‟ species richness is higher in less anthropized environments such as old and young fallows, however, landscapes formed by different land use types including alley croppings and pastures, may provide important resources to maintaining populations of solitary wasps and bees in regions where the original vegetation was entirely removed. Additionally, crops may benefit from the proximity of forest fragments by reduced pest problems